Different responses of greenhouse gas emissions to straw application at different seasons in Northeast China - Shuang, Liang; Hao, Zhang (Penerbit Universiti Kebangsaan Malaysia, 2019)
Although straw return plays a role in regulating greenhouse gas (GHG) emissions from rice paddy fields, little quantitative information is available on the extent at different periods. In this study, gas samples were collected during the rice growing period from an in-situ experiment comprising three treatments: no straw return (CK); straw return in the autumn (SR-A), and; straw return in the spring (SR-S). The results showed that SR-A and SR-S enhanced CO2 and CH4 emissions, but reduced N2O emissions during the growing period. The total cumulative CO2 emissions over the entire growing period in the SR-S treatment reached 20,383.72 kg ha−1, significantly higher than those of the SR-A and CK treatments. CH4 emissions for all the growing periods were in the order SR-S > SR-A > CK. The CK and SR-S treatments released the most and least N2O during the different periods, respectively. The global warming potential (GWP) of CH4 released by the SR-S, SR-A and CK treatments reached 26,055.37 kg CO2 eq. ha−1, 12,643.27 kg CO2 eq.1, and 9,237.55 kg CO2 eq.1, accounting for 55.80%, 40.35%, and 35.99% of the total GWP, respectively. These results can contribute to management of agricultural GHGs in this region.